Resuscitative endovascular balloon occlusion of the aorta induced myocardial injury is mitigated by endovascular variable aortic control. Issue 3 (September 2019) - Beyer, Carl A.; Hoareau, Guillaume L.; Tibbits, Emily M.; Davidson, Anders J.; DeSoucy, Erik D.; Simon, Meryl A.; Grayson, John Kevin; Neff, Lucas P.; Williams, Timothy K.; Johnson, Michael Austin
Abstract : BACKGROUND: The cardiac effects of resuscitative endovascular balloon occlusion of the aorta (REBOA) are largely unknown. We hypothesized that increased afterload from REBOA would lead to cardiac injury, and that partial flow using endovascular variable aortic control (EVAC) would mitigate this injury. METHODS: Eighteen anesthetized swine underwent controlled 25% blood volume hemorrhage. Animals were randomized to either Zone 1 REBOA, Zone 1 EVAC, or no intervention (control) for 45 minutes. Animals were then resuscitated with shed blood, observed during critical care, and euthanized after a 6-hour total experimental time. Left ventricular function was measured with a pressure-volume catheter, and blood samples were drawn at routine intervals. RESULTS: The average cardiac output during the intervention period was higher in the REBOA group (9.3 [8.6–15.4] L/min) compared with the EVAC group (7.2 [5.8–8.0] L/min, p = 0.01) and the control group (6.8 [5.8–7.7] L/min, p < 0.01). At the end of the intervention, the preload recruitable stroke work was significantly higher in both the REBOA and EVAC groups compared with the control group (111.2 [102.5–148.6] and 116.7 [116.6–141.4] vs. 67.1 [62.7–87.9], p = 0.02 and p < 0.01, respectively). The higher preload recruitable stroke work was maintained throughout the experiment in the EVAC group, but not in the REBOA group. Serum troponin concentrations after 6 hours were higher in the REBOA group compared with both the EVAC and control groups (6.26 ± 5.35 ng/mL vs 0.92 ± 0.61 ng/mL and 0.65 ± 0.38 ng/mL, p = 0.05 and p = 0.03, respectively). Cardiac intramural hemorrhage was higher in the REBOA group compared with the control group (1.67 ± 0.46 vs. 0.17 ± 0.18, p = 0.03), but not between the EVAC and control groups. CONCLUSION: In a swine model of hemorrhagic shock, complete aortic occlusion resulted in cardiac injury, although there was no direct decrease in cardiac function. EVAC mitigated the cardiac injury and improved cardiac performance during resuscitation and critical care.